Climate Sin Stocks: Stock price reactions to global climate strikes - Ramelli Stefano; Ossola Elisa; Rancan Michela (Publications Office of the European Union, 2020)
The first Global Climate Strike on March 15, 2019 has represented a historical turn in climate activism. We investigate the cross-section of European stock price reactions to this event. Looking at a large sample of European firms, we find that the unanticipated success of this event caused a substantial stock price reaction on high-carbon intensity companies. These findings are likely driven by an update of investors' beliefs about the level of environmental social norms in the economy and the anticipation of future developments of climate regulation.
Keywords: Q01; G14; G40; G23; 330; Climate risks; stock returns; event study; environmental preferences; sustainable finance; investor attention